The Potential of Food Terrorism towards Halal Ecosystem - Jamaludin, Mohammad Aizat (2020)
The approaching of megatrend 2050, challenges have emerged in the food sector and it is predicted that main issues would be the shortage of food supply and food contamination. In parallel to the Food and Agricultural Organization (FAO), that by 2050, with the increasing human population, the food supply would be affected as the sources are inadequate to cater. This crisis requires a comprehensive solution – necessitate a better food security policy, food safety and food defence. In other words, a focused policy that deals with safe food ecosystem must be implemented and strengthen by relevant authorities. In the Malaysian context, the National Safety Policy (2017) outlined the security assurance for the nation’s food supply under Strategy 17. However, the focus of the policy is only on the preparedness of rice commodity that needs to be adequate, whereas, newer threats is making their way beyond that scope. Therefore, this review will discuss the potential of food terrorism, its concept and implication within the halal ecosystem. To achieve this objective, this study is qualitatively carried out by utilizing fully library research relating to food terrorism. The data is being analysed to conclude the findings. Based on the study, we found that food terrorism is indeed a real threat jeopardizing consumer safety, and moreover, causing negative implications towards the local, regional and global halal ecosystem. Therefore, proactive measures needed to be taken to ensure the security of food and this aligned with the objective of sharia to preserve human’s life by having adequate, nutritious, halal and safe food.